2002
DOI: 10.1074/jbc.m202015200
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal Triacylglycerol Transfer Protein Is Required for Lumenal Accretion of Triacylglycerol Not Associated with ApoB, as Well as for ApoB Lipidation

Abstract: The assembly of very low density lipoproteins in hepatocytes requires the microsomal triacylglycerol transfer protein (MTP). This microsomal lumenal protein transfers lipids, particularly triacylglycerols (TG), between membranes in vitro and has been proposed to transfer TG to nascent apolipoprotein (apo) B in vivo. We examined the role of MTP in the assembly of apoB-containing lipoproteins in cultured murine primary hepatocytes using an inhibitor of MTP. The MTP inhibitor reduced TG secretion from hepatocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
119
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 58 publications
11
119
1
1
Order By: Relevance
“…6). Very recently, Kulinski et al (10) proposed that MTP might be involved in TG accumulation in luminal space in ER in murine primary hepatocytes, and Raabe et al (11) also suggested the same hypothesis from the observations about MTP knock-out mice. In our experiments, verapamil did not show any effect on MTP.…”
Section: Verapamil Specifically Inhibits the Secretion Of Apob-contaimentioning
confidence: 70%
See 2 more Smart Citations
“…6). Very recently, Kulinski et al (10) proposed that MTP might be involved in TG accumulation in luminal space in ER in murine primary hepatocytes, and Raabe et al (11) also suggested the same hypothesis from the observations about MTP knock-out mice. In our experiments, verapamil did not show any effect on MTP.…”
Section: Verapamil Specifically Inhibits the Secretion Of Apob-contaimentioning
confidence: 70%
“…It was clearly shown that newly synthesized apoB in cells lacking MTP failed to associate with lipids and subsequently the apoB was degraded (8). It is also reported that MTP has a molecular chaperon-like activity (9) and contributes to TG transfer from cytosol to lumen of the endoplasmic reticulum (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we observed functional and structural differences between CG9342 and human MTP, possibly reflecting known differences in intracellular and extracellular aspects of vertebrate and invertebrate lipid transport and metabolism. The identification of invertebrate orthologs of human MTP may enable structural and functional dissection of the multiple roles of human MTP in apoB assembly as well as apoB-independent effects on intracellular lipid trafficking (23)(24)(25) (26) as implemented by the SignalIP V2.0 server on the web. The amino terminus of mature human MTP was based on data reported by Shoulders et al (27).…”
mentioning
confidence: 99%
“…The production of apolipoprotein B (apoB)-containing lipoproteins by the liver is mainly regulated by the relative amount of de novo synthesized apoB that is translocated into the endoplasmic reticulum and assembled into a secretion-competent lipoprotein particle (7)(8)(9)(10). MTP, an intraluminal protein in the endoplasmic reticulum (11), plays an important role in regulating the assembly and secretion of apoB-containing lipoproteins (12)(13)(14)(15)(16). In humans, the loss of MTP function blocks the production of apoB-containing lipoproteins by both the intestine and the liver (11).…”
mentioning
confidence: 99%